Techno-Economic Analysis of Simplified Microcrystalline Cellulose Process - Kari Mikael Vanhatalo; Kari Eino Parviainen; Olli Pekka Dahl (BioResources, 2014)
This work presents a techno-economic analysis of two modelled microcrystalline cellulose (MCC) production facilities, a stand-alone mill, and a mill integrated into a chemical pulp mill, with annual production levels of 30,000 tons/year. These results indicate that both options can be very profitable when the return on investment and the added value of the purchased chemical pulps are used as indicators. However, the integration of MCC production will yield about 19% greater net profit than the non-integrated alternative. Integration also reduces the economic risk of investment, since operation of the MCC plant can be halted for maintenance and chemical pulp can be produced in a normal manner.